Simulating policy options for universal child allowances in Ghana - Martin Evans (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper considers the case for universal child allowances in Ghana. It follows findings from an earlier study of 14 middle income countries that examined optimal approaches to reduce child poverty using universal categorical child allowances. The paper describes the demographic profiles that will influence the impact of a universal child allowance: 67 per cent of Ghanaian households contain children, and those households contain 82 per cent of the total population, spreading the impact of a small allowance - funded by a fixed budget - over a very large proportion of the population. Income differences at the margins of the poverty line were found to be small and robustness and sensitivity tests were done to accompany simulation. Simulations found that individual level allowances reduce poverty more than household level allowances. Such individual level allowances weighted to the bottom 40 per cent are found to have better poverty reduction than allowances weighted to young children.
Keywords: D31; H53; I32; I38; 330; poverty; social policy; children; micro-simulation